PENGARUH MEDIA AUGMENTED REALITY TERHADAP KEMAMPUAN MENYIMAK PADA ANAK USIA 5-6 TAHUN DI TK BINTANG CENDEKIA PEKANBARU - Dera Puspawati; Febrialismanto Febrialismanto; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations in the field it can be seen that the ability to listen to children aged 5-6 years is still in the category of developing. So it is necessary to use augmented reality media. This study aims to determine the effect of augmented reality media on listening ability. This research was conducted at the Bintang Cendekia Scholar Pekanbaru Kindergarten. This study uses an experimental method with a pretest-posttest control group design with a total sample of 30 children and uses saturated sample techniques. Data collection techniques in this study are observation techniques. The data analysis technique used t-test using SPSS 21 program. The results of data analysis were obtained tcount = 7.886 is greater than t table = 2.048 with a significance of 0,000 <0.05. It can be concluded that there are differences in the ability to listen before and after the use of augmented reality media. The influence given by the augmented reality media based on the N Gain formula was 61.07%.Key Words: Listening, Augmented Reality